Challeging factors of the GBI (Green Building Index) application for heritage building / Nurafifah Adlina Amran and Mohd Nurfaisal Baharuddin - Amran, Nurafifah Adlina; Baharuddin, Mohd Nurfaisal (2023)
The most effective option for old buildings is "green adaptive reuse," which can improve productivity. The Association of Consulting Engineers Malaysia (ACEM) and PAM (Pertubuhan Arkitek Malaysia/Malaysian Institute of Architects) created the Green Building Index, an environmental evaluation system for structures. The Green Building Index is Malaysia's first in-depth assessment system for evaluating the environmental efficiency and design of Malaysian structures. There are several problems faced in implementing the GBI (Green Building Index) in heritage buildings, such as a lack of awareness among clients, consultants, and contractors, a lack of sustainable materials, techniques, and procedures, and a lack of knowledge and expertise. The research objective is to investigate the most challenging factor of the application GBI (Green Building Index) for heritage buildings and to suggest the most challenging factor of the application GBI (Green Building Index) for heritage buildings. This study uses qualitative method to collect data through interview. Through the findings of the study, out of the 3 main factors asked, all of the factors that are critical are analysed, which are lack of education and knowledge of the GBI (Green Building Index), lack of awareness among clients, consultants, and contractors, and lack of sustainable materials, techniques, and procedures.